House in the modern home - Daniels , Inge (London and New York : Routledge, 2020)
This book explores every aspect of the home and daily life in Japan - from decoration, display, furniture and the tatami mat, to eating, sleeping, gift-giving, recycling and worship.
Keywords: Architecture and anthropology